A CMOS fully differential ring VCO with active inductors and I/Q outputs. Issue 4 (26th December 2018) - Zhang, Changchun; Wang, Xinwen; Fang, Junliang; Zhang, Ying; Tang, Lu
Abstract: A novel four‐stage fully differential ring voltage controlled oscillator (VCO) is presented and implemented in 0.18 μm CMOS technology. The fully differential delay cell is chosen over the pseudo‐differential one to avoid the cross‐coupling pair, increase the oscillation frequency and improve common‐noise suppression. The inductive shunt peaking technique with active inductors instead of its passive counterpart is used to expand the bandwidth of the delay cell and then increase the oscillation frequency of the VCO without the expense of excessive area. The current bleeding transistor pair is connected in shunt with the tuning transistor pair in order to make sure the VCO oscillate over the entire tuning voltage with proper phase noise. Measurement results show that, from a single voltage supply of 1.8 V and an occupied area of 475 μm × 275 μm, the proposed VCO achieves an oscillation frequency range from 3.25 to 4.2 GHz with the optimum phase noise of −92.28 dBc/Hz at 1 MHz and an optimum FOM of −154.80 dBc/Hz.